2017
DOI: 10.3390/molecules22061008
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparative Study of the Inhibitory Effects of Mangiferin and Its Aglycone Norathyriol towards UDP-Glucuronosyl Transferase (UGT) Isoforms

Abstract: Mangiferin (MGF), the predominant constituent of extracts of the mango plant Mangifera Indica L., has been investigated extensively because of its remarkable pharmacological effects. In vitro recombinant UGTs-catalyzed glucuronidation of 4-methylumbelliferone (4-MU) was used to investigate the inhibition of mangiferin and aglycone norathyriol towards various isoforms of UGTs in our study, which evaluated the inhibitory capacity of MGF and its aglycone norathyriol (NTR) towards UDP-glucuronosyltransferase (UGT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Our results demonstrated MGF metabolite norathyriol shown more potent effect to decrease intracellular TG content, as well as regulating SREBP-1c activity in SO-induced TG accumulation HepG2 cells, compared with MGF. It is reported that norathyriol was a competitive inhibitor of protein tyrosine phosphatase 1B ( Ding et al, 2014 ) and UDP-glucuronosyltransferase isoforms ( Sun et al, 2017 ) to improve glucose homeostasis. In this study, we firstly reported the lipid lowering effect of norathyriol and its underlying mechanism in regulating hepatic lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated MGF metabolite norathyriol shown more potent effect to decrease intracellular TG content, as well as regulating SREBP-1c activity in SO-induced TG accumulation HepG2 cells, compared with MGF. It is reported that norathyriol was a competitive inhibitor of protein tyrosine phosphatase 1B ( Ding et al, 2014 ) and UDP-glucuronosyltransferase isoforms ( Sun et al, 2017 ) to improve glucose homeostasis. In this study, we firstly reported the lipid lowering effect of norathyriol and its underlying mechanism in regulating hepatic lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of drug-metabolic enzymes in drug combination therapies is considered an important origin of adverse effects. It can lead to withdrawal of several approved drugs from the markets, causing clinical problems and economic losses [ 7 , 26 ]. Along with the upsurge of herb–drug combinations, inhibition of herbs towards drug-metabolic enzymes in HDIs has been raised as an important reason that limits clinical applications of herbs and drugs [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro results referring the inhibitory effects of herbs based on IC 50 and K i values are not sufficient to provide relevance to in vivo results especially at clinical levels. This is because more various metabolic pathways and other elimination pathways except metabolism (e.g., urinary excretion or biliary excretion) can be involved in HDIs in vivo [ 26 , 31 , 32 ]. For example, discrepancies of HDI for milk thistle, garlic extract, Panax quinquefolius , and Panax ginseng between in vitro and clinical results have been reported [ 18 , 31 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations